QUR'ANIC SOCIAL TRANSFORMATION IN AL-AZHAR INTERPRETATION - N, Abd Muid; Jamiluddin, Ach (Institut PTIQ Jakarta, 2020)
This research proves that Hamka, in Interpretation Al-Azhar, supports the concept of Transformative Islam by: first reinterpreting important Islamic theology with interpretations that makes speculative theoretical debates in Islamic theology more applicable to arousing human awareness of their role on earth; Second, it supports Islam's alignment with social, economic and political conditions and considers it to be as important as the Godhead in Islam. Third, Formulating Islamic transformation action through Ta'muruna bi al ma'ruf, tanhawna 'an al-munkar, and tu'minuna billah, but more emphasis on tu' minuna bil Lah.